Strategies of Kindergarten Teachers and Parents in Preparing Children's School Readiness: Academic, Social, and Emotional Perspectives - Mardiah, Lisda Yuni; Wulan, Sri; Akbar, Zarina (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to investigate the strategies employed by kindergarten teachers and parents in preparing children's school readiness in the Batang Angkola District, considering the local context and related social dynamics. Design/methods/approach – Utilizing a qualitative descriptive method, the research combines a descriptive approach to outline existing phenomena with a qualitative approach to explore the meanings and interpretations of the strategies used. Data were collected through direct interviews with several kindergarten teachers and parent representatives in kindergartens and surrounding areas in the Batang Angkola District. Additionally, secondary data related to supporting theories on children's school readiness were utilized. Findings – The findings reveal that both kindergarten teachers and parents are not fully prepared for children's school readiness. This is evidenced by the non-alignment of teachers' educational backgrounds with early childhood education and the parents' primary focus on academic readiness, often neglecting other critical aspects such as social and emotional development. Furthermore, the strategies implemented by kindergarten teachers and parents fail to holistically address the needs of children during the transition process. Research implications/limitations – The study is limited to the Batang Angkola District and may not be generalizable to other regions. These findings highlight areas in educational practices that require improvement and suggest the need for further research to develop more effective strategies for holistic school readiness preparation. Practical implications – The insights gained from this study provide guidance for the development of more holistic and integrated school readiness preparation programs that can better support children during their transition to school. These programs should aim to balance academic learning with social, emotional, and physical development to ensure well-rounded preparedness. Originality/value – This research sheds light on the specific challenges faced by kindergarten teachers and parents in the Batang Angkola District, emphasizing the importance of a holistic approach to school readiness that includes academic, social, and emotional aspects. By addressing these challenges, the study contributes to the broader understanding of effective strategies for early childhood education in similar contexts. Paper type Case study